Advancements in Lab-on-a-Chip Technology for Biomedical Applications - Nair, Arjun (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 12 No 1&2 (2025): Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
Lab-on-a-chip (LOC) technology has revolutionized biomedical diagnostics, drug discovery, and personalized medicine by enabling miniaturized, automated, and highly efficient biochemical analyses. By integrating microfluidics, biosensors, and advanced materials, LOC devices provide rapid, low-cost, and high-throughput solutions for complex biological and chemical processes. These devices have demonstrated significant potential in disease diagnostics, point-of-care testing, organ-on-a-chip models, and drug screening, facilitating real-time analysis with minimal sample requirements. Recent advancements in LOC technology have led to the development of paper-based microfluidics, droplet-based digital microfluidics, and 3D-printed LOC platforms, enhancing sensitivity, specificity, and scalability. The incorporation of novel biosensors, such as electrochemical, optical, and magnetic sensors, has further improved the detection of biomolecules, enabling early disease diagnosis and continuous health monitoring. Additionally, organ-on-a-chip models have emerged as a promising alternative to traditional in vitro and animal testing, offering more physiologically relevant conditions for studying human diseases and drug responses. Despite its vast potential, LOC technology faces challenges such as fabrication complexity, standardization, cost-effectiveness, and regulatory approvals for clinical applications. The integration of artificial intelligence (AI) and the Internet of Medical Things (IoMT) is expected to enhance data processing, automation, and remote diagnostics, further advancing the field. This review provides an in-depth analysis of recent innovations in LOC technology, its applications in biomedical sciences, and the future directions that can shape next-generation diagnostic and therapeutic solutions.